(untitled) (Boston, 1998)
This volume presents a practical laboratory-based manual of molecular protocols designed for the screening of biodiversity of plant and animal tissue. The book brings together the work of 35 European laboratories working under the EU biotechnology program.
Keywords: Biodiversity,Molecular biology,Molecular probes,Đa dạng sinh học,Sinh học phân tử; Measurement,Technique,Thiết bị đo lường,Kỹ thuật